2014
DOI: 10.1016/j.rbre.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of respiratory impairment in patients with systemic lupus erythematosus with the six-minute walk test

Abstract: Six-minute walk testOxygen saturation Respiratory function test Questionnaires a b s t r a c t Objective: Evaluate SLE stable patients, without overt respiratory compromise, by means of 6MWT. Casuistic and methods: Forty-five stable SLE patients were enrolled. The ATS/ERS protocol for 6MWT, was used and two parameters with cut-off points were chosen. Results: Forty-two patients were women. The mean age was 39 ± 11.4 years; mean duration of disease, 121 ± 93.1 months; mean value of MRC, 2 ± 0; mean FVC, 85.9 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Because SLE is a rare disease, performing research in a large number of patients from one center is often not possible. saturation and the distance traveled by the patients in 6MWT [24]. In both studies, a significantly smaller distance in 6MWT was covered by patients with SLE.…”
Section: Discussionmentioning
confidence: 66%
“…Because SLE is a rare disease, performing research in a large number of patients from one center is often not possible. saturation and the distance traveled by the patients in 6MWT [24]. In both studies, a significantly smaller distance in 6MWT was covered by patients with SLE.…”
Section: Discussionmentioning
confidence: 66%
“…Balsamo et al revealed a significant decrease in distance walked in 6MWT in Brazilian premenopausal female SLE patients and found a positive correlation between exercise capacity and quality of life [25]. Additionally, Leite et al presented that the SpO 2 physiological parameter was superior used to finding respiratory impairment in patients during the 6-MWT [26]. However, they did not assess how other physiological parameters changed in SLE patients at 6-MWT.…”
Section: Discussionmentioning
confidence: 99%
“…Background This study investigated physical activity, peripheral muscle strength, exercise capacity, sleep, fatigue, anxiety and depression in patients with systemic lupus erythematosus (SLE). Material and Methods Twenty-six patients with SLE, median age 32.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) years, and 29 healthy individuals, median age 30 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) years, were included. Exercise capacity (6-minute walk test (6MWT)), peripheral muscle strength (dynamometer), physical activity (Mi Band 4 smart band), fatigue (Fatigue Severity Scale (FSS)), anxiety and depression (Hospital Anxiety Depression scale (HAD)), quality of life (SLE-specific QOL scale (SLEQoL)) and sleep (Pittsburgh Sleep Quality Index (PSQI)) were assessed.…”
Section: Introductionmentioning
confidence: 99%